Mechanical properties of eccentrically compressed columns strengthened with textile-reinforced concrete under the coupled action of chloride salt corrosion and loading. (November 2021) - Li, Shichang; Yin, Shiping; Wang, Luchen; Hu, Xiangqian
Highlights: TRC (Textile-reinforced concrete) has good crack control performance for eccentric column. Failure modes and bearing capacity of eccentric column can be improved by TRC. The coupling of chloride and load has a negative effect on TRC-strengthened columns. The eccentricity and previous load have an influence on the strengthening effect of TRC. Abstract: Building structures located in tidal areas are more vulnerable to damage due to the coupled effect of the chloride exposure during dry/wet cycling and loading during their service life; thus, such structures need to be repaired and strengthened. In this study, to examine the mechanical properties of textile-reinforced concrete (TRC)-strengthened eccentrically loaded columns under the coupled action of chloride corrosion and loading, eccentric compression testing of 10 TRC-strengthened rectangular reinforced concrete (RC) columns is conducted, and the influence of parameters such as the eccentricity and previous load level on the effect of TRC strengthening is considered. The results show that TRC strengthening can effectively inhibit the development and extension of cracks in eccentrically compressed specimens placed in a corrosive environment (due to chloride salt) while exhibiting a satisfactory crack control. With increasing eccentricity, the utilization rate of the tensile strength of the textile increases, and the contribution of the TRC strengthening layer to the specimen strength increases. With the increase in the previous load level, the strengthening effect of the TRC becomes more notable. Finally, the changes in the microstructure in the TRC strengthening layer under different previous load levels are analysed through scanning electron microscopy (SEM), and the damage degradation mechanism of the TRC strengthening effect is explored from a microscopic viewpoint.